Modified R–L model‐based protection for VSC‐DC distribution lines. Issue 13 (19th January 2018) - Jia, Ke; Li, Meng; Bi, Tianshu; Liu, Bohan; Li, Wei; Yang, Qixun
Abstract : An R–L model‐based line protection algorithm is proposed for the voltage source converter (VSC)‐DC distribution systems. Overviews of DC distribution topology and the fault characteristics are investigated. The feasibility of the R–L model for DC distribution networks is analysed. To decrease errors and increase numerical stability, a new variable acquisition method and a new fault distance estimation equation are proposed with the characteristics of VSC‐DC distribution systems. Simulation results on power systems Computer Aided Design/Electromagnetic Transients including DC (PSCAD/EMTDC) verify the feasibility and accuracy of the proposed protection. It is shown that the protection can efficiently distinguish the internal faults with an operation time < 20 ms and error within 1%. For nearby faults, the protection can trip within 8 ms. The proposed protection can meet both the speed and the selectivity requirements with a low sampling frequency and therefore can be a potential option for the industry application.